MODEL OF CUSTOMER SATISFACTION FOR IMPROVING CUSTOMER LOYALTY - Tjahjadi, Dicky; Nandan Limakrisna (Dinasti Publisher, 2022)
This study aims to determine the influence of service quality, product quality, corporate image on customer satisfaction and customer loyalty. The population in this study were 341 customers of Corporate Banking Division in Bank CIMB Niaga with a sample of 100 customers. Sampling was carried out using the slovin formula. Analysis method used path analysis. The results showed that the product quality, service quality and corporate image partially has significant influence on customer satisfaction. Product quality, service quality, and corporate image simultaneously has significant influence on customer satisfaction. For product quality, service quality, corporate image and customer satisfaction partially has significant influence on customer loyalty. Product quality, service quality, corporate image and customer satisfaction simultaneously has significant influence on customer loyalty. Customer satisfaction did not mediate effectively the influence of service quality, product quality, and corporate image on customer loyalty